All that is solid melts into air : the experience of modernity - Berman, Marshall (Penguin books, 1988)
The political and social revolutions of the nineteenth century, the pivotal writings of Goethe, Marx, Dostoevsky, and others, and the creation of new environments to replace the old—all have thrust us into a modern world of contradictions and ambiguities. In this fascinating book, Marshall Berman examines the clash of classes, histories, and cultures, and ponders our prospects for coming to terms with the relationship between a liberating social and philosophical idealism and a complex, bureaucratic materialism.